QARAQALPAQ NAQÍL-MAQALLARÍ QURAMÍNDA “BAS” KOMPONENTLI SOMATIKALÍQ BIRLIKLER - Mámbetalieva, Q.A. (SCIENCE and SOCIETY, 2025)
In this article, we wanted to analyze the somatic units with the concept of "bas" in proverbs from the linguistic and cultural point of view. Proverbs are closely related to people's lifestyle and culture, and they are examples of somatic units in people's everyday life, somatic units in their actions.
Keywords: proverb; idiom; somatic unity; meaning of emotional-expressiveness